Boracéia Biological Station: an ornithological review - Cavarzere, Vagner; Moraes, Gabriel Parmezani; Silveira, Luís Fábio (Papéis Avulsos de Zoologia, 2010)
Boracéia Biological Station, near the city of Salesópolis, SP, is located in one of the most well-defined centers of endemism in eastern Brazil - the Serra do Mar Center. While the station was established only in 1954 under the auspices of the Museu de Zoologia da Universidade de São Paulo, the avifauna of this locality had already attracted the attention of ornithologists by the 1940s, when the first specimens were collected. Here we describe the ornithological history of the Boracéia Biological Station with a review of all the bird species recorded during more than 68 years, including recent transect and mist-netting records. Boracéia's records were found in museums, literature and unpublished reports that totaled 323 bird species when recent data is also considered. Of these, 117 are endemic to the Atlantic forest and 28 are threatened in the state. Although there are a few doubtful records that need to be checked, some species are the only sightings in the state. Boracéia includes a recently discovered species near the station site and is extremely important for the conservation of Atlantic forest birds.